Comparison of aerobic and anaerobic abilities between kata and kumite athlete in karate - Nickytha, Ersha Ady; Fitri, Mustika; Sultoni, Kuston (Universitas Nusantara PGRI Kediri, 2019)
The present study aims at examining the differences in aerobic and anaerobic abilities between kata and kumite athlete, in an attempt to reveal a variation in each category, due to the discrepancies in characteristics of movement for match requirements. Therefore, a comparative study with quantitative approach was employed, using causal-comparative design, which involves 20 karate athletes, with 10 people from each category as participants selected through the use of purposive sampling. In addition, data analysis technique required the use of Independent Sample t-test, and the result indicated significant differences in the level of alpha 0.05, with aerobic ability possessing a value Sig. 0.253, which shows the absence of significant differences between kata and kumite athletes. Furthermore, the data of anaerobic ability was recorded as Sig. 0.860, suggesting no significant differences as well.